Phonon promoted charge density wave in topological kagome metal ScV6Sn6 - Yong Hu; Junzhang Ma; Yinxiang Li; Yuxiao Jiang; Dariusz Jakub Gawryluk; Tianchen Hu; Jérémie Teyssier; Volodymyr Multian; Zhouyi Yin; Shuxiang Xu; Soohyeon Shin; Igor Plokhikh; et al. (Nature Communications, 2024)
Abstract Charge density wave (CDW) orders in vanadium-based kagome metals have recently received tremendous attention, yet their origin remains a topic of debate. The discovery of ScV6Sn6, a bilayer kagome metal featuring an intriguing $$\sqrt{3}×\sqrt{3}×3$$ 3 × 3 × 3 CDW order, offers a novel platform to explore the underlying mechanism behind the unconventional CDW. Here, we combine high-resolution angle-resolved photoemission spectroscopy, Raman scattering and density functional theory to investigate the electronic structure and phonon modes of ScV6Sn6. We identify topologically nontrivial surface states and multiple van Hove singularities (VHSs) in the vicinity of the Fermi level, with one VHS aligning with the in-plane component of the CDW vector near the $$\bar{K}$$ K ¯ point. Additionally, Raman measurements indicate a strong electron-phonon coupling, as evidenced by a two-phonon mode and new emergent modes. Our findings highlight the fundamental role of lattice degrees of freedom in promoting the CDW in ScV6Sn6.